Analisis Struktur Modal Perbankan Syariah di Indonesia - Mila Istiqomah; Supriyanto (JURNAL PENELITIAN, 2017)
This study aims to analyze the factors that influence the capital structure of sharia banking in Indonesia during the period 2011–2015. This research uses quarterly time series data, which are analyzed by multiple regression. The sample used in this research consists of eight sharia banks in Indonesia, selected through purposive sampling. The independent variables in this study are company size, company growth rate, income stability, and asset structure, while the dependent variable is the capital structure. The analytical tool used is multiple linear regression analysis. The results show that company size, company growth rate, income stability, and asset structure have a significant effect on capital structure. The F-test results indicate that the variables of company size, company growth rate, income stability, and asset structure simultaneously affect the capital structure. Based on the results of this study, it can be concluded that the factors considered by banks in determining their capital structure are the composition of assets and the income earned. Therefore, sharia banking in Indonesia needs to optimize both income and total assets owned.